1998
DOI: 10.1128/aem.64.9.3539-3543.1998
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Frankia Strains in Root Nodules of Plants from the Families Elaeagnaceae and Rhamnaceae

Abstract: Partial 16S ribosomal DNAs (rDNAs) were PCR amplified and sequenced from Frankia strains living in root nodules of plants belonging to the families Elaeagnaceae and Rhamnaceae, includingColletia hystrix, Elaeagnus angustifolia, an unidentified Elaeagnus sp., Talguenea quinquenervia, and Trevoa trinervis. Nearly full-length 16S rDNAs were sequenced from strains ofFrankia living in nodules of Ceanothus americanus, C. hystrix, Coriaria arborea, and Trevoa trinervis. Partial sequences also were obtained from Frank… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…An analysis of 1307 positions of the 16S rRNA gene showed that this strain differs from the closest known Frankia by almost 4%, indicating that it represents a new lineage in the Frankia assemblage. The other strains did not differ greatly on the 16S rRNA gene from already known strains nevertheless they clustered in the two different groups of the Elaeagnaceae-Rhamnaceae infective strains [25,32] signifying a high relative diversity.…”
Section: Discussionmentioning
confidence: 79%
“…An analysis of 1307 positions of the 16S rRNA gene showed that this strain differs from the closest known Frankia by almost 4%, indicating that it represents a new lineage in the Frankia assemblage. The other strains did not differ greatly on the 16S rRNA gene from already known strains nevertheless they clustered in the two different groups of the Elaeagnaceae-Rhamnaceae infective strains [25,32] signifying a high relative diversity.…”
Section: Discussionmentioning
confidence: 79%
“…Although somewhat controversial, it is generally accepted that a 16S rRNA gene sequence similarity greater than 97% indicates microbes that are likely to be members of the same species and 95% indicates the same genus [Stackebrandt and Goebel, 1994]. Furthermore, phylogenetic analyses (data not shown) indicated that these clones do not fall within any of the known Frankia clades as defined previously in the literature [Clawson et al, 1998;Huguet et al, 2001;Normand et al, 1996]. Two other Actinobacterial groups were cloned with 5 clones most closely related to the uncultured Rubrobacter sp.…”
Section: S Rrna Gene Clone Libraries From Atacama Soilsmentioning
confidence: 84%
“…Besides two sequence groups including strains BMG5.2, BMG5.5 and BMG5.12 and strains BMG5.3, BMG5.4, BMG5.10 and BMG5.11, respectively, together with known Elaeagnus infective strains, strain BMG5.6 described a third branch in the tree confirming that this strain represents a new lineage in the Frankia assemblage, and that the diversity of Elaeagnus ‐compatible Frankia is wider than previously recognized. This diversity is noteworthy in view of the relatively narrow geographic distribution of the analyzed soils, and suggests that the overall diversity of Frankia colonizing Elaeagnaceae and Rhamnaceae is wider than previously thought [32]. In a study on the diversity of Frankia colonizing Elaeagnaceae and Rhamnaceae , Clawson et al [32] detected two main types of sequences, these differing at only one position in a 378 bp fragment of the 16S rRNA gene, from nodules and isolated strains deriving from ten plant species of eight genera recovered in France (two strains from different geographic areas), USA (one nodule), New Zealand (one nodule), Argentina (one strain) and Chile (three nodules and five isolates from seven different geographic areas).…”
Section: Discussionmentioning
confidence: 58%
“…An analysis of 1307 positions of the 16S rRNA gene showed that this strain differs from the closest known Frankia by almost 4%, indicating that it represents a new lineage in the Frankia assemblage. The other strains did not differ greatly on the 16S rRNA gene from already known strains nevertheless they clustered in the two different groups of the Elaeagnaceae–Rhamnaceae infective strains [25,32] signifying a high relative diversity.…”
Section: Discussionmentioning
confidence: 80%